Determinants of crowdfunding activity and the role of culture: a cross-national analysis - Bernardino, Susana (2022)
Internet and other computer-based information system technologies have been used to develop new forms of funding mechanisms. Crowdfunding (CF) is an alternative fundraising tool that relies on a platform that allows entrepreneurs to interact directly with a large amount of potential funders. This mechanism could be attractive both for individuals who are looking for funding (crowdfunders) and for investors who are looking for application opportunities (crowdfundees). As the CF market has reached very different activity levels across the globe, this research aims to understand if national culture variations affect the dynamics of CF market activity. To attain this objective, we construct a database that includes: i) data from a survey of the Global Alternative Finance Market Benchmarking Report; ii) values by country of Hofstede's cultural dimensions; and, iii) some control variables. Based on regression analysis, the results show that CF variations across countries are influenced by national culture, specifically lower uncertainty avoidance, individualism, and long-term orientation.